2015
DOI: 10.1016/j.jcp.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Detection and classification from electromagnetic induction data

Abstract: In this paper we introduce an efficient algorithm for identifying conductive objects using induction data derived from eddy currents. Our method consists of first extracting geometric features from the induction data and then matching them to precomputed data for known objects from a given dictionary. The matching step relies on fundamental properties of conductive polarization tensors and new invariance properties introduced in this paper. A new shape identification scheme is developed and tested in numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 27 publications
0
87
0
Order By: Relevance
“…The extension of the analysis to nonsmooth boundaries will form part of our future work. However, numerical evidence from computing Mˇˇ for objects with edges indicates that our results are also likely to hold for such objects …”
Section: Complete Asymptotic Expansion Of (Hα−h0)(x) As α →mentioning
confidence: 99%
See 2 more Smart Citations
“…The extension of the analysis to nonsmooth boundaries will form part of our future work. However, numerical evidence from computing Mˇˇ for objects with edges indicates that our results are also likely to hold for such objects …”
Section: Complete Asymptotic Expansion Of (Hα−h0)(x) As α →mentioning
confidence: 99%
“…Remark To be able to characterise an unknown conducting permeable object from measurements of ( H α − H 0 )( x ), using Theorem , a range of alternative approaches are possible, which include adapting the algorithms described by Ammari and Kang for the EIT problem or using a statistical classifier . In the latter case, we assume that we have a set of possible candidate objects and we follow Ammari and Kang, to put these in canonical form such that the description B α = α B + z , for each object, implies that the origin for ξ coincides with the object's centre of mass and that the determinant of the Póyla‐Szegö tensor associated with B (ie, scriptTfalse(μrfalse)false[Bfalse] for μ r ≠1 and scriptTfalse(0false)false[Bfalse] for μ r =1) is equal to 1 .…”
Section: Complete Asymptotic Expansion Of (Hα−h0)(x) As α →mentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of a known admissible class A in our algorithm is related to the dictionary matching algorithms that have been recently investigated in a series of works by Ammari and his collaborators [2,3,13], where some a priori known base shapes form a dictionary for the reconstruction. We also note that comparable indicator functions are used in a recent work [15] for reconstructing the acoustic scatterers at small scale and regular scale, respectively.…”
Section: Scheme IImentioning
confidence: 99%
“…In applied mathematics and analysis, previous studies by [1,14,15,16,17,18,19] have shown that the perturbation due to the presence of the conducting objects can be represented by asymptotic formulas and PT is actually the dominant term in the formula. The asymptotic formula and the corresponding PT are generally not the same for different systems.…”
Section: Introductionmentioning
confidence: 99%